Confidence in repair of obstetric anal sphincter injuries and objective assessment in obstetricians. Issue 4 (2015) - Napoé, Gnankang Sarah; Foust-Wright, Caroline E.; Pulliam, Samantha J.; Melamed, Alex; Batalden, Rebecca Posthuma; Berkowitz, Lori R
No abstract available